Performance of 3-Phase 9-Level CHB and NPC Inverters - Aljaism, Wadah (European Journal of Applied Sciences, 2026)
This study conducts a comprehensive qualitative comparison of nine-level Cascaded H-Bridge (CHB) and Neutral-Point-Clamped (NPC) multilevel inverter architectures for medium-voltage three-phase networks operating at 380 V RMS and 50 Hz. Under the same circumstances, MATLAB/Simulink modelling assesses harmonic distortion, device count, switching and conduction losses, capacitor balancing difficulty, and overall waveform quality. To guarantee a fair comparison, matching carrier frequencies and Nearest Level Modulation (NLM) are employed. According to the results, at 4 kHz switching, the CHB inverter generates less Total Harmonic Distortion (THD) in line-to-line voltages—roughly 2.1% as opposed to 3.7% for NPC. Despite having more semiconductors, loss estimation shows that CHB has about 12% lower overall losses because of less voltage stress per switch. Despite providing a single DC-link supply, NPC has more common-mode voltage swings and a bigger neutral-point imbalance. Results indicate that while NPC is still useful in situations where isolated supplies are not feasible, CHB is better suited for modular energy sources (such as PV and battery-based systems).